Construction of a Yeast Three‐hybrid System for Identifying Escherichia coli Proteins Interacting With Small Non‐coding RNAs. (17th March 2015) - Bak, Geunu; Hong, Soon Kang; Jung, Juyeon; Kim, Kwang‐sun
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10234-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>